2023
DOI: 10.3390/foods12061236
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Extrusion Treatments, Quality Assessments, and Kinetics Degradation of Enzyme Activities during Storage of Rice Bran

Abstract: Over the years, extrusion has been a multi-step thermal technique that has proven to be the most effective process to stabilize rice bran (RB). This study aimed to investigate the effects of extrusion treatment and temperature (15, 25, and 40 °C) on the storage stability, lipid oxidation, peroxidase, and peroxide values, free fatty acids, fatty acid composition, and protein variations of RB over 60 days. The study offers novel insights into the changes in RB’s protein and amino acid compositions during extrusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The development differs from the results of the study [11], where a rational ratio of the basic components of extruded animal feed was determined without varying the moisture and lipid content. Also, the development differs from the works [27,28], where the influence of the moisture and fat content of the raw material on the technological parameters of extruded products was investigated, because protein-containing by-products of the oil-producing industry in combination with grain raw materials were chosen as raw components. The extruded protein-fat system of the developed composition has a high crude protein content (Table 2), as well as high porosity due to the rational ratio of moisture and lipids in the raw material (Fig.…”
Section: Discussion Of the Results Of Determining The Influence Of Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…The development differs from the results of the study [11], where a rational ratio of the basic components of extruded animal feed was determined without varying the moisture and lipid content. Also, the development differs from the works [27,28], where the influence of the moisture and fat content of the raw material on the technological parameters of extruded products was investigated, because protein-containing by-products of the oil-producing industry in combination with grain raw materials were chosen as raw components. The extruded protein-fat system of the developed composition has a high crude protein content (Table 2), as well as high porosity due to the rational ratio of moisture and lipids in the raw material (Fig.…”
Section: Discussion Of the Results Of Determining The Influence Of Th...mentioning
confidence: 99%
“…Using the example of rice bran, the authors of the work [28] found that the content of proteins, lipids and moisture of the raw material affects the process of extrusion of the raw material. In particular, an increase in moisture content contributes to an increase in the yield strength of the extrudate, its better formation and, accordingly, a more even distribution of pressure inside the extruder.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Figure 1B,C shows that the carbonyl value and the malondialdehyde content of brown rice with high moisture content samples increased with storage time, indicating that the cell membrane integrity was gradually compromised, and the quality deteriorated. Specifically, the carbonyl values and the malondialdehyde content of brown rice samples at 15 • C storage for 90 days were significantly lower than those stored at 20 • C and 25 • C. Similarly, Liu et al [14] discovered that the carbonyl values of brown rice stored at 15 • C for 270 days were significantly lower than those at 25 • C and 35 • C. Additionally, Muhammad et al [26] found that the elevated temperature led to increased oxidation and malondialdehyde levels in rice bran over the course of storage. Consequently, it could be inferred that japonica brown rice with high moisture content at a temperature of 15 • C storage retarded the growth of its peroxide value, carbonyl value, and malondialdehyde content, which were beneficial to retaining its freshness.…”
Section: Pasting Propertiesmentioning
confidence: 97%
“…Protein can be denatured in extrusion due to high temperature and shear force, but many studies suggest no significant effect on the protein content of RB. 61…”
Section: Effect Of Extrusion On the Physical And Nutritional Qualitiesmentioning
confidence: 99%